Bio-Imperialism : Disease, Terror, and the Construction of National Fragility - D'Arcangelis, Gwen Shuni (Book collections on Project MUSE., 2021)
"Bio-imperialism focuses on an understudied dimension of the war on terror-the fight against bioterrorism. This component of the war included the enlistment of bioscientists and health workers to augment U.S. biodefense and disease control infrastructure, advancing U.S. control over biological resources on a global scale. The book argues that U.S. imperial ambitions drove this move, aided by U.S. government and mass media narratives that deployed gendered and raced discourses of terrorism, U.S. vulnerability, and white femininity-intertwined with discourses about disease and technoscientific progress. The result was further entrenchment of tropes of Arabs, Muslims, and other racially marginalized communities as embodying terror and disease; the revamping of research industries conducting dangerous lab experiments on pathogens; the militarization of public health and its deployment of feminized bodies in service of warmongering; and decreased autonomy for global south nations to administer health care to their populations. Yet as U.S. bio-empire pressed forward, so too did new forms of confrontation-its critics rejected its hegemonic narratives, electing instead to build transnational solidarities and engage in collective struggle to oppose the mobilization of the bioscience and public health fields for war and empire. Bio-imperialism is a sobering look at how the war on terror impacted the world in ways that we are only just starting to grapple with"--